The Meaning of Vertical Housing for Balinese People, the Debate between Cultural Demands and the Need for Urban Housing in Bali, Indonesia - Dharmayanty, Ni Luh Putu Dessy; Paturusi, Syamsul Alam; Dwijendra, Ngakan Ketut Acwin; Dewi, Ni Ketut Agusinta (International Journal of Psychosocial Rehabilitation, 2020)
In the midst of fears of an increase in the conversion of agricultural land into residential areas, the implementation of housing needs program for urban communities in the region of Bali, with one solution to build a vertical housing, apparently has not been able to attract the interest of Balinese Hindus to choose residential in vertical housing. Faced with a dilemma, the economic needs and demands of indigenous culture and traditions that are believed, with the implementation of the Panca Yadnya (five ritual ceremonies), in their daily lives, is a unique local wisdom, which requires facilities even in the vertical housing. The purpose of this research is to find out what exactly is the meaning of vertical housing for Balinese who are Hindu? Because until now the Balinese have not made vertical housing as an option for their residence. With a qualitative method, through tracing Balinese perceptions and the processes of cognition, affection and cognition, from residents of vertical housing and people who need housing, it is hoped that from this research it will be known what exactly the meaning of vertical housing is for Balinese.